Pertamina's Quasi-Monopoly : How Restrictions on Basic Fuel Imports Impact the Downstream Oil and Gas Investment - Maharani, Dewi Nadya; Muzakki, Fauzan; Hartati S, Sawitri Yuli; Setiyono, Setiyono; Efrianto, Gatot (Dinasti Research, 2025)
This study discusses the implications of quasi-monopolies that arise due to Pertamina's dominance in the management of the oil and gas sector, especially related to the policy of regulating fuel imports through the Circular Letter of the Ministry of Energy and Mineral Resources Number T-19/MG.05/WM. M/2025 dated July 17, 2025. A quasi-monopoly occurs when market dominance is achieved through administrative policies that limit market access for other business actors. This study uses a normative juridical approach, with qualitative-descriptive analysis of laws and regulations, legal literature, and policy documents. The results of the analysis show that the fuel import regulation policy that gives preference to Pertamina can hinder private investor participation, increase the risk of unfair competition, and create legal uncertainty, thereby contributing to declining investment interest. This study recommends policies to ensure fair market access, import transparency, contractual legal certainty, and periodic evaluation of policy impacts. The implementation of these recommendations is expected to minimize quasi-monopolies, encourage a healthy investment climate, and ensure sustainable national energy management